Looking for the obvious: motorcycle taxi services in Sub-Saharan African cities - (:unkn) unknown (My University, 2020)
Motorcycle taxis (MCT) have been present in many cities of Sub-Saharan Africa for several decades. This paper aims to answer two questions: How can we objectify the massive and lasting development of a “motorcycle taxi model” in the cities of SSA? How does this model function in practice? First, the spread of motorcycle taxis in Sub-Saharan Africa is examined by using an internet-based bibliometric analysis of academic output and local press articles. Second, the functioning of the industry and the informalization rationales at work in the deployment of the motorcycle taxi model are analyzed on the basis of a field study in Lomé, the capital of Togo. The bibliometric analysis of the academic output shows the presence of MCT in 14 countries over a 30 year period, and that of the local press almost doubles the number of countries. It also provides some temporal reference points and suggests some reasons for MCT deployment. Three main features of the functioning of the MCT industry in Lomé are identified: the equivocal attitude of the State, the heterogeneous characteristics of the players, and the strong and multifaceted linkages of MCT with formal activities. The results from this research provide evidence that the development of the motorcycle taxi model in SSA is closely associated with globalization and informalization processes.
Keywords: African Research